Image Content Retargeting : Maintaining Color, Tone, and Spatial Consistency /: Maintaining Color, Tone, and Spatial Consistency. (2016) - Artusi, Alessandro; Banterle, Francesco; Aydın, Tunç Ozan; Panozzo, Daniele; Sorkine-Hornung, Olga
No abstract available